Transformasi Pembelajaran Pendidikan Agama Islam di Era Society 5.0: Integrasi Teknologi Digital dan Literasi Spiritual - Rizal, Saiful (Lembaga Yasin AlSys, 2026)
The era of Society 5.0 demands that the education sector, including Pendidikan Agama Islam (PAI), undergo transformation and adapt to the rapid development of digital technologies without neglecting the importance of spiritual literacy as the foundation for students’ character formation. This article aims to analyze forms of PAI instructional transformation through the utilization of digital technology integrated with the strengthening of spiritual literacy. The research method employed is library research with a descriptive–analytical approach to literature related to PAI, educational technology, and the discourse on Society 5.0. The findings indicate that the transformation of PAI in the Society 5.0 era is manifested through the use of digital platforms, the deployment of artificial intelligence–based media, the development of hybrid curricula, and the implementation of interactive learning models combined with the cultivation of spiritual values grounded in critical reflection and the internalization of religious teachings. The integration of digital technology and spiritual literacy is assessed as capable of addressing contemporary educational challenges while preserving the core objective of nurturing noble character. The article concludes that the development of innovative, relevant, and character-oriented PAI learning models depends heavily on the capacity of educators and educational institutions to manage the synergy between digital technology and spiritual literacy, and it is expected to serve as a reference for the formulation of policies and instructional practices in PAI in the Society 5.0 era.